Recent progress in cassava agronomy research in China - Tian, Yinong; Lee, Jun; Zhang, Weite; Fang, Baiping (International Center for Tropical Agriculture, 1995)
In recent years, cassava agronomy research in China has emphasized soil fertility maintenance, erosion control, planting methods and date of planting and harvesting. The research was conducted in cooperation between the Guangxi Subtropical Crops Research Institute, the South China Academy of Tropical Crops, and the Upland Crops Research Institute with CIAT. Results of three long-term fertility trials indicate that fertilizer application markedly increased cassava root yields. But different varieties showed a different response to fertilizers. SC205 was more responsive to fertilizer application than SC201 or SC124; high rates of fertilizers resulted in high yields of SC205, but not of SC201 or SCI 24. The experiments also showed that during four cropping cycles of cassava in southern China, N was the most important nutrient for increasing cassava root yields, but that K and in some cases P also became increasingly important. Application of farm yard manure or burned soil, in addition to medium levels of chemical fertilizers, had no significant effect on increasing cassava root yields. Experiments on soil erosion control conducted in Hainan and Guangxi showed that contour ridging, intercropping with peanut, or barrier strips of Brachiaria pasture were the most effective practices for reducing soil erosion when planting cassava. Intercropping of cassava with peanut or cassava with seed watermelon increased income more than 65-200% compared with cassava monoculture. Cassava grown with Stylosanthes guianensis barriers reduced soil erosion 14-27%, while increasing income 23-43%. Among several methods of planting cassava, vertical planting resulted in more rapid sprouting than horizontal or inclined planting, especially during periods of drought, but root yields were not significantly different. Among planting on the flat, or on single-row or double-row ridges, there was not much difference in germination and root yield. Research to determine the optimum time of planting and harvest of cassava, conducted at SCATC, showed that when cassava was harvested at 8 months after planting, highest yields were obtained when cassava was planted during the spring (Feb- May); however, when cassava was harvested at 12 months, time of planting had no consistent effect on yield.